Применение режима „свой - чужой” при распознавании алгоритмов синтеза моделей в системах многоуровневого социоэкологического мониторинга - Колос, П.А. (Міжнародний науково-навчальний центр інформаційних технологій і систем НАН та МОН України, 2009)
This article deals with the investigation of "friend or foe" regime in the pattern recognition technology to solve the problem of determining the synthesis model algorithm of the input object in multilevel monitoring information systems for the system structure coordination according to the characteristics of the object primary data informative descriptions.